Efek Ekstrak Buah Srikaya (Annona Squamosa L.) Terhadap Penurunan Tekanan Darah Pada Mencit (Mus musculus) - Fitriani, Fitriani; Walanda, Daud K.; Ningsih, Purnama (Universitas Tadulako, 2017)
The research aim is to determine the effect of sugar-apple fruit extract on the reduction of blood pressure in mice as the tested animal. The sugar-apple extract was obtained through maceration method with the ratio of sugar-apple fruit powder and water 1:10, after that the heating was done to produce the extract in solid form, then the potassium content was measured by using a spectrophotometer and male mice were induced by adrenaline injection, namely epinephrine. The mice were divided into 5 groups randomly with different treatment. P1 was as a negative control (-), P2, P3, P4 were given the sugar-apple extract with the doses of 50, 100 and 150 mg/kg BW respectively, while P5 was as positive control (+) that was given captopril. The data obtained were analyzed by the statistical analysis, the analysis of variance (ANOVA) and was followed by Duncan’s test. The result obtained that on preclinical testing revealed that the sugar-apple extract was proven to reduce the blood pressure of mice and the effective extract was the concentration of 150 mg/kg with the average blood pressure of 48 mmHg.